Clinical characteristics and risk factors for Mycoplasma pneumoniae pneumonia in children - Zhao, Xueqi; Lv, Jiajia; Wu, Min; Wu, Qun (Frontiers in Pediatrics, 2024)
BackgroundMycoplasma pneumoniae (M. pneumoniae) is one of the most common pathogens of community-acquired pneumonia (CAP) in children. Although Mycoplasma pneumoniae pneumonia (MPP) is considered a self-limiting disease, severe MPP (SMPP) occurs in some cases. This study aims to analyze clinical features of MPP and to explore predictive indicators in the early stage of M. pneumoniae infection.MethodsWe retrospectively enrolled patients with MPP and non-MPP (NMPP) hospitalized to the Department of Pediatrics, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine from 2023 to 2024. A total of 757 children with CAP were divided into MPP group and NMPP group. Patients with MPP included SMPP group and mild MPP (MMPP) group. Demographic and clinical characteristics as well as laboratory and imaging tests were deemed to be baseline data within 24 h after admission. We compared differences between MPP group and NMPP group as well as SMPP group and MMPP group. To exclude the impacts of age and gender, analysis of covariance and Logical regression was used to account for the baseline differences in the probability between MPP group and NMPP group, SMPP group and MMPP group. Logistic regression analysis was used to screen markers as potential early clinical predictors. ROC curves were applied to estimate the diagnostic and predictive value of different indicators for SMPP group.ResultsAmong the 757 cases of CAP, 464 cases were MPP group and 226 cases were SMPP group. There were significant differences in hospital stay and fever duration between the MPP and NMPP groups. Compared to NMPP group, MPP group exhibited higher levels of platelet count (PLT), heparin-binding protein (HBP), erythrocyte sedimentation rate (ESR), immunoglobulin G (IgG) (P < 0.05). The levels of C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), serum ferritin (SF), prothrombin time (PT), fibrinogen (Fg), interleukin-5 (IL-5) and Gamma interferon (IFN-γ) were significantly increased in SMPP group compared to MMPP group. PT, Fg, SF, IL-5 and IFN-γ were independent risk factors for SMPP group. Significantly, IL-5 and IFN-γ served as reliable predictive indices of SMPP.ConclusionsNotable differences were observed in both clinical characteristics and serum inflammatory markers between the MPP group and the NMPP group, as well as between the SMPP group and the MMPP group. Consequently, PT, Fg, SF, IL-5 and IFN-γ hold the potential to be employed as efficacious predictors for SMPP.